2011
DOI: 10.1136/gutjnl-2011-300154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selective COX-2 inhibitor andHelicobacter pylorieradication on precancerous gastric lesions

Abstract: This population-based intervention trial revealed that celecoxib treatment or H pylori eradication alone had beneficial effects on the regression of advanced gastric lesions. No favourable effects were seen for H pylori eradication followed by celecoxib treatment. Trial registration HARECCTR0500053 in accordance with WHO ICTRP requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
158
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 31 publications
1
158
1
Order By: Relevance
“…5 Selective cyclooxygenase-2 (COX-2) inhibitors have beneficial effects on preventing inflammation-related carcinogenesis and on the regression of advanced GC. 6,7 COX-2 induces the production of PGE 2 , which upregulates NR4A2 expression via sequential activation of the Rho, protein kinase A (PKA), and nuclear factor-jB signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…5 Selective cyclooxygenase-2 (COX-2) inhibitors have beneficial effects on preventing inflammation-related carcinogenesis and on the regression of advanced GC. 6,7 COX-2 induces the production of PGE 2 , which upregulates NR4A2 expression via sequential activation of the Rho, protein kinase A (PKA), and nuclear factor-jB signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…27). A recent subgroup analysis indicated that the elimination of H. pylori can reduce gastric cancer incidence in older participants and in those with advanced baseline histopathology (28). From 2002 to 2006, another randomized, placebo-controlled trial was conducted in Linqu to study the effects of H. pylori eradication and a COX-2 inhibitor (celecoxib) in a 2 Â 2 factorial design with 1,024 participants (29).…”
Section: Studies On Etiology and Prevention Of Gastric Cancer In Linqmentioning
confidence: 99%
“…In 2004, a total of 1,024 eligible participants were invited to the intervention trial according to the selection and exclusion criteria described previously (24). Briefly, the trial included participants ages 35-64 years with H. pylori-positive and baseline histology of chronic atrophic gastritis, intestinal metaplasia, indefinite dysplasia, or dysplasia.…”
Section: Study Populationmentioning
confidence: 99%
“…In 2002, an initial screening program was conducted in Linqu County, a high-risk area of gastric cancer in China, with interview, carbon-13 urea breath test ( 13 C-UBT), upper endoscopy and pathologic diagnosis (24). In 2004, a total of 1,024 eligible participants were invited to the intervention trial according to the selection and exclusion criteria described previously (24).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation